2020
DOI: 10.1097/01.aoa.0000652960.08788.6d
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Choice for Different Postcesarean Delivery Analgesic Protocols on Opioid Consumption: A Randomized Prospective Clinical Trial

Abstract: (Reg Anesth Pain Med. 2019;44:578–585) Pain management after cesarean delivery is typically selected by the physician without patient input. Shared decision-making between provider and patient may improve patient care. A recent study showed patients who requested a higher intrathecal morphine dose for cesarean delivery had increased opioid requirements and greater postoperative pain, regardless of the actual dose administered. This study aimed to determine whether postoperative oxycodone requirements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Having a choice did not impact on rescue opioid consumption, but women were very good in predicting their actual opioid needs. Choosing high-dose intrathecal morphine was associated with increased rescue analgesia and more vomiting [45,46]. Apart from one study [44], all studies used basic analgesia with NSAIDs [42,43,46] or a combination of NSAIDs and paracetamol [45].…”
Section: Neuraxial Adjuvant Drugsmentioning
confidence: 99%
“…Having a choice did not impact on rescue opioid consumption, but women were very good in predicting their actual opioid needs. Choosing high-dose intrathecal morphine was associated with increased rescue analgesia and more vomiting [45,46]. Apart from one study [44], all studies used basic analgesia with NSAIDs [42,43,46] or a combination of NSAIDs and paracetamol [45].…”
Section: Neuraxial Adjuvant Drugsmentioning
confidence: 99%
“…e results revealed that patients who requested the larger dose required more supplemental opioids and reported more pain than those who requested the smaller dose. Another study reported similar results, with patients choosing a higher dose (300 mcg intrathecal morphine + single dose oral gabapentin 600 mg) requiring more rescue opioids than those selecting a medium dose (150 mcg) or low dose (50 mcg) [27].…”
Section: Identification Of Women At Risk Of Severe Postoperative Painmentioning
confidence: 69%
“…Our results demonstrated that recent surgeries (especially 2015-2020) were strongly associated with the utilization of neuraxial morphine. The trend in neuraxial morphine use is important in establishing benchmarks and could provide invaluable information to help clinicians and patients in shared decision-making for postcesarean delivery analgesia [13].…”
Section: Discussionmentioning
confidence: 99%